Soluble epoxide hydrolase inhibition exhibits antihypertensive actions independently of nitric oxide in mice with renovascular hypertension - Kopkan, Libor; Husková, Zuzana; Sporková, Alexandra; Varcabová, Šárka; Honetschlägerová, Zuzana; Hwang, Sung Hee; Tsai, Hsing-Ju; Hammock, Bruce D; Imig, John D; Kramer, Herbert J; Bürgelová, Marcela; Vojtíšková, Alžběta; et al. (Kidney & blood pressure research, 2012)
OBJECTIVE: The present study was performed to examine whether the blood pressure (BP)-lowering effects of soluble epoxide hydrolase (sEH) inhibition in two-kidney, one-clip (2K1C) Goldblatt hypertension are nitric oxide (NO) dependent. METHODS: Mice lacking the endothelial NO synthase (eNOS) gene (eNOS-/-) and their wild-type controls (eNOS+/+) underwent clipping of one renal artery. BP was monitored by radiotelemetry and the treatment with the sEH inhibitor cis-4-[4-(3-adamantan-1-yl-ureido)cyclohex-yloxy]-benzoic acid (c-AUCB) was initiated on day 25 after clipping and lasted for 14 days. Renal concentrations of epoxyeicosatrienoic acids (EETs) and their inactive metabolite dihydroxyeicosatrienoic acids (DHETs) were measured in the nonclipped kidney. Renal NO synthase (NOS) activity was determined by measuring the rate of formation of L-[(14)C]citruline from L-[(14)C]arginine. RESULTS: Treatment with the sEH inhibitor elicited similar BP decreases that were associated with increases in daily sodium excretion in 2K1C eNOS+/+ as well as 2K1C eNOS-/- mice. In addition, treatment with the sEH inhibitor increased the ratio of EETs/DHETs in the nonclipped kidney of 2K1C eNOS+/+ as well as 2K1C eNOS-/- mice. Treatment with the sEH inhibitor did not alter renal NOS activity in any of the experimental groups. CONCLUSIONS: Collectively, our present data suggest that the BP-lowering effects of chronic sEH inhibition in 2K1C mice are mainly associated with normalization of the reduced availability of biologically active EETs in the nonclipped kidney and their direct natriuretic actions.
Keywords: Animals; epoxid hydrolasy; Mice, Knockout; myši knockoutované; Enzyme Inhibitors; Mice; renovaskulární hypertenze; myši; synthasa oxidu dusnatého, typ III; Male; Hypertension, Renovascular; inhibitory enzymů; Nitric Oxide Synthase Type III; oxid dusnatý; Antihypertensive Agents; zvířata; mužské pohlaví; antihypertenziva; Mice, Inbred C57BL; Nitric Oxide; Epoxide Hydrolases; myši inbrední C57BL